Construction of a Ce3+ doped CeO2/Bi2MoO6 heterojunction with a mutual component activation system for highly enhancing the visible-light photocatalytic activity for removal of TC or Cr(vi). Issue 6 (7th May 2019) - Yang, Gui; Liang, Yujun; Li, Kai; Yang, Jian; Xu, Rui; Xie, Xianjun
Abstract : A synergetic effect of a mutual activation system enhancing the photo-oxidation and reduction ability of a C-BMO heterojunction. Abstract : Developing heterojunction photocatalysts with more efficient charge carrier transfer and separation is of huge significance in environmental engineering. Herein, a Ce 3+ doped CeO2 /Bi2 MoO6 (C-BMO) heterojunction was designed and fabricated via a facile molten salt-assisted route. Under 5 W white LED light irradiation, the 20% C-BMO heterojunction exhibited a much higher maximum degradation rate of tetracycline (TC) (91%) as compared with the individual CeO2 (58%) and Bi2 MoO6 (44%) within 180 min. Meanwhile, the removal rate of the 20% C-BMO heterojunction for dichromate (Cr(vi )) (97%) was higher than that of CeO2 (30%) and Bi2 MoO6 (19%) within 90 min. The enhanced capabilities were ascribed to a synergetic effect of the mutual activation system based on the formation of a Ce 3+ /Ce 4+ redox couple between the 0D CeO2 nanoparticles and 2D Bi2 MoO6 nanosheets. The facile molten salt-assisted strategy and efficient performance endow the C-BMO heterojunctions with high potential for photo-oxidation and reduction of pollutants from actual wastewater.